Intentions to use contraceptives in Pakistan: implications for behavior change campaigns - Agha Sohail (BMC, 2010)
Abstract Background Since 1990-91, traditional method use has increased at a faster rate in Pakistan than modern method use. The importance of hormonal methods or the IUD has diminished and that of traditional methods has increased in the method mix. There is a need to identify factors motivating and deterring the adoption of specific family planning methods among married men and women in Pakistan. Methods In addition to social and demographic characteristics of respondents, a representative household survey collected information on psychological correlates of family planning behavior from 1,788 non-pregnant wives and 1,805 husbands with not-pregnant wives. Males and females were from separate households. Principal components analysis was conducted to identify the underlying constructs that were important for each gender. Multinomial logistic regression analysis was conducted to determine the correlates of male and female intentions to use contraceptive methods. Results Amongst women, the perception that her in-laws support family planning use was the strongest determinant of her intentions to use contraceptive methods. A woman's belief in the importance of spacing children and her perception that a choice of methods and facilities with competent staff were available were also powerful drivers of her intentions to use contraceptive methods. The strongest obstacle to a woman's forming an intention to use contraceptive methods was her belief that family planning decisions were made by the husband and fertility was determined by God's will. Fears that family planning would harm a woman's womb lowered a woman's intentions to use methods requiring procedures, such as the IUD and female sterilization. The perception that a responsible, caring, husband uses family planning to improve the standard of living of his family and to protect his wife's health was the most important determinant of a man's intention to use condoms. A husband's lack of self-efficacy in being able to discuss family planning with his wife was the strongest driver of the intention to use withdrawal. A man's fear that contraceptives would make a woman sterile and harm her womb lowered his intention to use modern contraceptive methods. Conclusions These findings highlight the importance of having secondary target audiences such as mothers-in-law and husbands in family planning behavior change campaigns implemented in Pakistan. Campaigns that stress the importance of child spacing are likely to have an impact. Client perceptions of the quality of care are important determinants of intentions to use contraceptive methods in Pakistan. Client concerns that the IUD and sterilization procedures might harm a woman's womb and cause sterility should be addressed. The findings suggest that there is a need to assess the actual quality of service delivery in Pakistan.